Una asociación de roedores del tránsito Eoceno/Oligoceno próxima a Süngülü, Lesser Caucasus, Turkey - Bruijn, Hans DE; Ünay, Engin; Saraç, Gerçek; Yïlmaz, Ali (Coloquios de Paleontología, 2003)
The assemblage of rodents from Süngülü that will be described below contains two genera and species of Ctenodactylidae, one genus and species of Dipodidae and seven genera representing eight species of Muridae. Three genera and seven species are new. The composition of the assemblage shows that this rodent fauna from Anatolia differs in many respects from that of Europe and Central Asia and is therefore endemic. The age as inferred from the fauna is Latest Eocene or Earliest Oligocene.